Glycosylated Amphiphilic Calixarene‐Based Detergent for Functional Stabilization of Native Membrane Proteins. Issue 19 (20th May 2019) - Dauvergne, Julien; Desuzinges, Elodie Mandon; Faugier, Clarisse; Igonet, Sébastien; Soulié, Marine; Grousson, Emilie; Cornut, Damien; Bonneté, Françoise; Durand, Grégory; Dejean, Emmanuel; Jawhari, Anass
Abstract: Structure‐function and drug discovery studies of membrane proteins (MPs) require their extraction from cell membranes. Here we report the synthesis and use of novel glycosylated amphiphilic calixarene‐based detergent, named CALX‐173‐GK, for native membrane protein stabilization. It consists of a nonionic polar part with three saccharide groups, a calixarene ring and an aliphatic tail of seven carbon atoms. Micellization, shape and self‐assemblies were investigated. The function of three native MPs was conserved, enhanced and stabilized overtime when CALX‐173‐GK was used as a solubilization additive. Taken together, the use of this novel glycosylated amphiphilic detergent confirms the added value of combining calixarene and glycosides groups to improve functional stability of MPs. This work also illustrates the advantage of associating solubilizing and stabilizing molecules, providing a new avenue for stabilization of functional membrane proteins. Abstract : Glycosylated amphiphilic calixarene‐based detergent for co‐solubilization and stabilization of functional membrane proteins. Combining calixarene and glycosides groups can improve functional stability of membrane protein targets such as transporters, GPCR and 7TM protein. This is of high interest to structure function studies and may enable drug discovery of difficult to produce native membrane proteins.